Hydrogen bonding-tuned hydroxo-bridged tetra-copper Cu4(bipy)4-cluster supramolecular network to layered coordination polymer. Issue 31 (28th July 2020) - Zhang, Jian; Chen, Yang-Yang; Tan, Chunhong; Ma, Xiao; Wang, Xiao-Feng; Ou, Guangchuan
Abstract : Hydrogen bonds influence the transformation of the Cu4 -cluster⋯ligand hydrogen net to the layered coordination polymer. Abstract : Three tetranuclear Cu(ii ) coordination compounds have been synthesized by the self-assembly of copper(ii ) nitrate with N/O donating bi-ligands through ammonia aqueous/ethanol mixture solution reaction. Single crystal structural analyses have shown that the three compounds feature chair-like hydroxo-bridged tetra-copper(ii ) cluster: symmetric [Cu4 (bipy)4 (OH)4 (H2 O)2 ] 4+ in 1, asymmetric [Cu4 (bipy)4 (OH)4 (H2 O)(1, 3-DBC)] 2+ in 2, and symmetric [Cu4 (bipy)4 (OH)2 (1, 2-BDC)2 ] 2+ in 3 (bipy = 2, 2′-bipyridineand H2 BDC = benzene dicarboxylic acid). Three bitopic benzene dicarboxylic ligands (1, 4-DBC 2−, 1, 3-DBC 2−, and 1, 2-DBC 2− ) act as a hydrogen bond acceptor, a mono-dentate terminal ligand, as well as a bi-dentate bridging ligand, respectively. Thus, hydrogen bonding plays a key role in influencing the transformation of the Cu4 -cluster⋯ligand hydrogen net to the 2-D layered metal–carboxylate coordination polymer. Meanwhile, the magnetic properties of 1 and 2 have been investigated.